Advancing Universal Health Coverage : What Developing Countries Can Learn from the Korean Experience? - Kwon, Soonman (World Bank, Washington, DC, 2018)
The Republic of Korea achieved universal health coverage in 1989, twelve years after the introduction of mandatory health insurance for employees in large corporations. Political legitimization of the authoritarian regime and rapid economic growth contributed to the rapid extension of health coverage. Most health care providers are private. In 2000, all insurance funds were merged into a single insurer, which improved the efficiency of risk pooling and equity in contribution payments. The single insurer system also provided the national health insurance system with the opportunity to strengthen its purchasing function. Nevertheless, the Korean health system faces challenges. Policy priority was given to population coverage, with low contributions and a limited benefits package, which resulted in insufficient financial protection of the insured. The rapid increase in private-sector providers has helped the supply readiness for universal health care, but has also engendered challenges to financial sustainability due to profit-seeking behavior and the overprovision of care, which was further exacerbated by fee-for-service payments. Korea’s health system also needs to be further reoriented to respond to the rapid aging of the population, and to the introduction in 2008 of a new public insurance scheme for long-term care.